Scientific Conceptualization and Ontological Difference - Ginev, Dimitri (De Gruyter, 2019)
Ginev works out a conception of the constitution of scientific objects in terms of hermeneutic phenomenology. Recently there has been a revival of interest in hermeneutic theories of scientific inquiry. The present study is furthering this interest by shifting the focus from interpretive methods and procedures to the kinds of reflexivity operating in scientific conceptualization. According to the book's central thesis, a reflexive conceptualization enables one to take into consideartion the role which the ontic-ontological difference plays in the constitution of scientific objects. The book argues for this thesis by analyzing the formation of objects of inquiry in a range of scientific domains stretching from highly formalized domains where the quest for objects' identities is carried out in terms of objects' emancipation from structures to linguistic and historiographic programs that avoid procedural objectification in their modes of conceptualization. The book sets up a new strategy for the dialogue between (the theories of) scientifc inquiry and hermeneutic phenomenology
10.1515/9783110605303
Keywords: Hermeneutik; Ontological difference; Ontologische Differenz; Reflexivität; hermeneutic situations; reflexivity; scientific objects; wissenschaftliches Objekt; PHILOSOPHY / Epistemology